Study of the optimum processing conditions of rainbow trout (Oncorhynchus mykiss) during the process of value adding - Visagie, Heleen (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1998.